(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
The present study was conducted on 200 healthy males among the age group of 17–25 years from Rajasthan state to observe the stage wise pattern of eruption of third molar for purpose of age estimation. Only those subjects were included in the study that did not show any diseased teeth or chronic illness in the form of endocrinal disorder or nutritional disorder or muscle skeletal disorder. The examination was done in good light with the help of torch and the teeth were considered erupted, in four stages with stage 0: No eruption with occlusal plane covered with alveolar bone; stage 1: When tip of crown of tooth penetrated the gum margin; stage 2: Partial eruption but not full occlusion; stage 3: Full eruption or full occlusion. All the data collected was entered into the excel sheet and the statistical analysis was done. The results were as follows: the mean age of eruption of left maxillary third molar was 21.0 ± 2.2 years, the mean age of eruption of right maxillary third molar was 21.0 ± 2.2 years, the mean age of eruption of left mandibular third molar was 21.0 ± 2.2 years, the mean age of eruption of right mandibular third molar was 21.0 ± 2.2 years.